Reliability of the modified Gartland classification in pediatric supracondylar humeral fractures - Ethan Choo; Jie Er Janice Soo; Rehena Sultana; Kenneth Pak Leung Wong; Neeraj Mishra; Summaiyya Hanum Ahamed; Kar Yee Catrin Kong; Arjandas Mahadev; Sashikumar Ganapathy; Khai Pin Lee; Shu-Ling Chong (Journal of Orthopaedic Reports, 2024)
Purpose: To assess the inter-rater reliability of the modified Gartland classification together with other radiological parameters for extension type supracondylar humerus fractures (SCHF) in children. Methods: A retrospective cohort study was conducted at a tertiary children's hospital in Singapore on children less than 12 years old with a diagnosis of extension-type SCHF between January 2017 and October 2017. Anteroposterior and lateral radiographs were assessed by fellowship-trained radiologist and orthopaedic surgeon. The radiographs were assessed for any breach of anterior cortex, breach of posterior cortex, presence of medial comminution, disrupted hourglass configuration and abnormal Baumann's angle. CorrespondingCohen's κ values were used to assess the level of inter-rater agreement. Results: We found an inter-rater agreement for the modified Gartland classification of κ = 0.141 (95 % CI, 0.049 to 0.233). Inter-rater agreement was κ = 0.654 (95 % CI, 0.493–0.815) for assessing a breach of anterior cortex was, κ = 0.357 (95 % CI, 0.135–0.578) for Baumann's angle, κ = 0.317 (95 % CI, 0.145–0.488) for a disrupted hourglass configuration, κ = 0.271 (95 % CI, 0.105–0.437) for a breach of posterior cortex and κ = 0.131 (95 % CI, −0.127 – 0.389) for the presence of medial comminution. Conclusion: We found a low inter-rater reliability for the modified Gartland classification. The breach of anterior and posterior cortex, Baumann's angle and hourglass disruption have higher inter-rater reliability.